Rocky Mountain Courage: Deadly Target - Book 2 - Goddard, Elizabeth (Thorndike, Maine : Center Point Large Print, 2022)
"Criminal psychologist Erin Larsons dreams of a successful career come to a screeching halt when she nearly loses her life in a boating accident and then learns that her mother tried to commit suicide. She leaves her job to care for her mother in Montana. At least there Erin is able to produce her podcast, which focuses on solving missing persons cold cases. Nathan Campbells father was investigating such a case when he was shot, and now Nathan needs to enlist Erins help to solve the case. Shes certainly good at what she does. The only problem? Shes his ex. As the two dig deeper, it becomes clear that they, too, are being targeted--and the answers to their questions are buried deep within the past Erin struggles to explain and longs to forget."--
Keywords: Psychologists -- Fiction; Podcasts -- Fiction; Cold cases (Criminal investigation) -- Fiction; Mothers and daughters -- Fiction; Suicide -- Fiction; Boating accidents -- Fiction; Criminal psychology -- Fiction; Montana -- Fiction; Christian fiction; Fiction; Romance fiction; Thrillers (Fiction); Christian fiction; Thrillers (Fiction); Romance fiction